The difference of serological responses between naturally infected, experimentally infected, and vaccinated cattle with Brucella abortus strain 19 vaccine - Sudibyo, Agus (Indonesian Animal Sciences Society, 1995)
The purposes of this research were to observe serological response differences of brucellosis between naturally infected, experimentally infected, and vaccinated cattle with Brucella abortus strain 19 vaccine . Identification of naturally infected cattle with B. abortus was carried out bacteriologically on milk samples collected from sero-positive brucellosis, while to determine serological responses blood samples were collected with 2 week interval from naturally and experimentally infected, and vaccinated cattle . Futhermore, the collected serum was examined serologically by using complement fixation test (CFT) and enzyme-linked immunosorbent assay (ELISA, indirect and competitive) . The result indicated that antibody titres (ELISA unit) of vaccinated cattle reached the peak at week -6 . This antibody titre was relatively lower and decreased quicker than naturally or experimentally infected cattle. Key words : Brucellosis, naturally infected cattle, vaccinated cattle, serological response